Driving forces for agroforestry uptake in Mediterranean Europe: application of the analytic network process - Lovrić, Marko; Rois-Díaz, Mercedes; den Herder, Michael; Pisanelli, Andrea; Lovrić, Nataša; Burgess, Paul J. (Springer, 2018)
The factors that determine the implementation of four alternative agroforestry practices or no agroforestry on a theoretical 200 ha farm in Mediterranean Europe were examined using an analytic network process (ANP) model. The four agroforestry practices considered were implementation of a form of (i) high natural and cultural value agroforestry, (ii) agroforestry with high value trees, and agroforestry for (iii) arable and (iv) livestock systems. The ANP model was developed in a participatory manner through a systematic series of quantitative questionnaires and workshops with agroforestry researchers. In general, all the Mediterranean agroforestry systems were associated with high benefits and opportunities, but also with high costs and high risks. The greatest benefits were attributed to high natural and cultural value agroforestry systems, which greatly contributed to the highest priority of this system. Overall ranking of priorities for the agroforestry management alternatives show robustness in the sensitivity analysis. The “no agroforestry” land use became the preferred option when costs were given a weighting of 0.50 or greater.
Keywords: Multiple criteria decision analysis (MCDA); Analytic network process (ANP); Mediterranean Drivers